DETECTION OF ANTIBODIES TO HIV IN UNSTIMULATED WHOLE SALIVA WITH IMMUNOCHROMATOGRAPHIC TEST KIT USED FOR SERUM. - Krithika, Chandrasekar Lakshmi; Sankarapandiyan, Sathasivasubramanian; Nagalingeswaran, Kumarasamy; Ganesan, Nalini (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: To determine the sensitivity and specificity for human immunodeficiency virus (HIV) antibodies in saliva using an immunochromatographic test kit used for serum for detection of antibodies specific to HIV-1/HIV-2 without any procedural optimization. Methods: A study was carried out in 40 HIV patients, and 40 HIV free volunteers. 2 ml of unstimulated saliva was collected, using drooling method into sterile pre-weighed plastic containers for 10 minutes. The samples were labeled with numbers and laboratory personnel were completely blind to the specimens and analyzed with a kit used to determine antibodies in serum/blood. Analysis was performed using immunochromatographic test kit-SD BIOLINE HIV-1/2 - rapid test procedure (WHO approved) - third generation, for the qualitative determination of antibodies of all isotypes specific to HIV-1 and HIV-2. No procedural optimization was done. Appropriate statistical analysis was performed. Results: Out of the 80 salivary samples, 38 were true positive, 40 were true negative and 2 were false negative for HIV. Sensitivity was 95%, specificity was 100%, positive predictive value of 100%, negative predictive value of 95% and disease prevalence of 50% were obtained. Conclusion: Saliva samples collected without any specialized devices, and any test modification can be used instead of serum in rapid test assays for screening of HIV 1 and 2 antibodies and serve as a diagnostic tool. Keywords: Saliva, Human immunodeficiency virus infection, Human immunodeficiency virus 1 and 2 antibodies, Rapid test.